Analysis of cholesterol levels in lipoprotein(a) with anion-exchange chromatography - Hirowatari, Yuji (The American Society for Biochemistry and Molecular Biology, 2010)
We previously established an analysis method for determining the cholesterol levels of five major lipoprotein classes [HDL, LDL, intermediate density lipoprotein (IDL), VLDL, and chylomicrons] in serum by an anion-exchange (AEX)-HPLC method, but lipoprotein(a) [Lp(a)], a well-known risk factor for atherosclerotic diseases, was not determinable. Therefore, we established new AEX-HPLC separation conditions for analyzing the cholesterol levels of six lipoprotein classes, including Lp(a). Serum lipoproteins were separated by HPLC with a diethylaminoethyl-ligand nonporous polymer-based column by elution with a stepwise gradient of the sodium perchlorate concentration. In this improved method, HDL, LDL, IDL, VLDL, chylomicrons, and Lp(a) were each eluted from the column. The cholesterol levels of the eluted lipoproteins were measured enzymatically by a postcolumn reaction. The within-day assay and between-day assay coefficients of variation for the lipoprotein cholesterol levels were in the ranges of 0.29–11.86% and 0.57–11.99%, respectively. The Lp(a) cholesterol levels determined by AEX-HPLC were significantly correlated with the amounts of Lp(a) protein measured by an immunoturbidimetry method available commercially (r = 0.9503, P < 0.0001). Taken together, this AEX-HPLC method may be effectively applied to the analysis of serum lipoproteins with high levels of Lp(a).